Post-transplant cancer: An epidemiological evaluation. Issue 3 (October 2020) - Francis, Anna; Au, Eric; Lim, Wai H; Wong, Germaine
Kidney transplantation is a lifechanging event for patients with end-stage kidney disease (ESKD) because it improves the quality of life and survival of these patients. However, it is not a cure and is not without complications. Transplant recipients have an excess risk of premature death (largely from cancer and cardiovascular disease (CVD)) by at least 10-times compared to the general population. Published work has identified cancer as one of the most important and feared outcomes in transplant recipients and is a key research priority recognised by both patients and health professionals. There is also convincing epidemiological evidence, suggesting the overall risk of developing cancer in the transplant population is approximately 2 to 3-fold higher compared to the age-matched general population. Unlike CVD, where the death rates have fallen considerably over the past decade in this population in response to better screening, preventative and intervention approaches, the excess risk of cancer-related deaths in transplant recipients remains at least 10-fold higher compared to cancer patients in the general population. The causes of the increased risk of death are unknown but may be a consequence of possible differences in tumour biology under the influence of immunosuppression. In this review, we will discuss the epidemiology of overall and site-specific cancer risk and death across different countries. We will also focus on the current evidence on the prevention and screening in our at-risk transplant candidates. Finally, management strategies of common cancers such as skin, post-transplant lymphoproliferative disease and solid organ cancers such as colorectal, breast and lung cancer will be evaluated.